Real time monitoring and analysis of tropical impact on PV performance based on LabVIEW architecture - Ya'acob, Mohd Effendy; Hizam, Hashim; Mohd Radzi, Mohd Amran (Engineering and Technology Publishing, 2014)
This paper presents a systematic, real-time and synchronized monitoring system for a 6-parameter tropical environmental elements and the energy performance of 3 types of Photovoltaic (PV) generator systems with the total generation capacity of 10kW. Based on recent studies, PV technology and application is economically viable to be adopted in tropical countries like Malaysia where it receives more than 6 hours of direct sunlight each day throughout the year. The task aims to feasibly integrate all 6 climatic parameters of Radiation, Temperature, Wind, Humidity, Light Intensity, and Rain using graphical LabVIEW software and cRIO as means of Data Acquisition and Real Time Monitoring (DART) system. This approach creates a unique platform interface for Solar PV Monitoring Station (SPMS) to capture measurement from multiple sources and analyze visually in real-time and synchronize mode which is the crucial aspect for rapid fluctuating data flow. This information will be the source of reference in designing a complete PV generator system cited in the tropics. The detail hardware integration, data flow process and SPMS system are further discussed.